2019
DOI: 10.1097/ncq.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of High-Reliability Principles on Hospital Units With Varying Safety Profiles

Abstract: Background: To prevent patient harm, health care organizations are adopting practices from other complex work environments known as high reliability organizations (HRO). Purpose: The purpose was to explore differences in manifestations of HRO principles on hospital units with high and low safety performance. Methods: Focus groups were conducted on units scoring high or low on safety measures. Themes were identified using a grounded theory approach, and responses were compared using qualitative thematic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2050
2050

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The study findings supported our hypotheses except for two only (Adaptability → Safety Participation and Resilience → Safety Participation). Our findings also expand on the theoretical proposition that mindful organizing, which is based on high-reliability organizations’ principles, can be the better fit for healthcare settings [ 12 ]. The notion of the proposed manifestation of mindful organizing practices in healthcare occupational settings is justified through our findings, as high-reliability organization principles are important to establish a safe healthcare environment [ 12 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The study findings supported our hypotheses except for two only (Adaptability → Safety Participation and Resilience → Safety Participation). Our findings also expand on the theoretical proposition that mindful organizing, which is based on high-reliability organizations’ principles, can be the better fit for healthcare settings [ 12 ]. The notion of the proposed manifestation of mindful organizing practices in healthcare occupational settings is justified through our findings, as high-reliability organization principles are important to establish a safe healthcare environment [ 12 ].…”
Section: Discussionsupporting
confidence: 79%
“…In the literature, studies have testified high-reliability organizations' (HROs) principles, i.e., mindful organizing in healthcare settings previously, and were associated with decreased medication errors, patient falls [8][9][10], and fewer accidents [11]. On the other hand, much of the qualitative evidence is available, which creates a scarcity of quantitative evidence for mindful organizing [12], its antecedents, and its outcomes [13]. Mindful organizing is the collective ability of the workforce to detect anomalies and act swiftly [14].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the analyzed studies have different options as to how to carry out such analyzes through the use of articles about nursing errors, adverse events notifications, or by analyzing the discourse of nursing professionals and obtaining their perceptions, a theoretical framework for substantiating interventions with a focus on patient safety culture. [8,[24][25][26][27][28][29][30][31][32][33] The possibility of promoting safe practices with a focus on risk-controlled healthcare has become pertinent, with the use of theories that help systematize nursing actions and create work processes with a strong theoretical foundation. The studies analyzed demonstrated that the process of changing practices must involve many agents of transformation, including nurses in direct care positions, nursing managers, students, and researchers.…”
Section: Discussionmentioning
confidence: 99%